Impact of the I-PASS Communication Method on Nurse Handover Quality in Hospital Settings: A Scoping Review - Agnes Stephania Penu; Ati Surya Mediawati; Hana Rizmadewi Agustina (Media Publikasi Cendekia Indonesia, 2026)
Effective handover communication is a crucial element in ensuring patient safety and continuity of care in clinical settings. Communication errors during handovers frequently lead to medical errors and adverse events. The I-PASS method was developed as a structured solution to address these challenges. This study aims to identify and synthesize evidence regarding the impact of implementing the I-PASS communication method on the quality of nurse handovers and its contribution to improving patient safety. A comprehensive literature search was conducted across four major databases (Science Direct, EBSCO, PubMed, and Scopus) from December 2024 to September 2025, using keywords such as